Spontaneous Hematoma of the Rectus Sheath: Urgent Embolization with Squidperi Liquid Embolic Device - Pierluca Torcia; Umberto G. Rossi; Silvia Squarza; Maurizio Cariati (Case Reports in Radiology)
We treated a 78-year-old female affected by nontraumatic spontaneous rectus sheath hematoma. We decided to perform the embolization with the new liquid agent Squidperi. Complete exclusion of the bleeding vessel was obtained without complications. Its use should be considered for treatment of nontraumatic rectus sheath hematoma.